Изюм: избранное / Татьяна Толстая - Толстая Татьяна Никитична (Книги Татьяны Толстой, 2007)
Экземпляры: аб. (2008) / Инвентарный номер: 52018 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 52 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6-44